Optical fiber sensors : advanced techniques and applications - Rajan, Ginu; Iniewski, Krzysztof, 1960- (Devices, circuits, and systems., 2015)
This book provides a fundamental understanding of the design, operation, and practical applications of fiber optic sensing systems. It describes the physical principles of, and latest developments in, optical fiber sensors, supplying detailed examples of the technology in use. Chapters address state-of-the-art topics and emerging areas of research including photonic crystal fiber sensors, micro- and nanofiber sensing, and liquid crystal photonics. The text draws upon the authors' extensive academic and industrial experience to deliver a comprehensive resource for students as well as scientists.